Gambar Terukur Konteks Pelestarian Arsitektur Masjid Ki Buyut Trusmi Cirebon - Alwin Suryono; Sudianto Aly; Amirani RS; Irma Subagyo; Yasmin Suriansyah (RUAS, 2022)
Several heritage buildings dating back the ancient history of the Ki Buyut Trusmi Cirebon site have been renovated and new buildings added. This paper aims to examine measured drawings related to the absence of original architectural documents. The method consists of field observation, expression of cultural meaning and significant architectural elements, as well as measured drawing studies. The heritage of Hindu-Javanese architecture has historical significance as a tomb complex based on an 1898 map, which is still in great demand by pilgrims. The significance of Hindu-Javanese architecture is related to the position of the mosque in the tomb complex, the gate leading to the complex, the complex gate, the barrier wall, and the complex fence. The manifestation of Javanese architecture can be found in the building of the mosque with a three-tiered roof, connected to the two-level roof porch, and a place for ablution on the north side. The social meaning is related to the traditional events of procession, roof changing, Trusmian and the commemoration of the birth of the Prophet Muhammad SAW which has been preserved until now. Measured drawings of the situation of the mosque and the plans of the building reveal that the appearance of the complex is strictly limited to the main prayer rooms (signifying Javanese architecture), not yet accompanied by gates and barrier walls (indicating Hindu-Javanese architecture), for historical-archaeological relics. The measured image of the main door of the mosque (amounting to a height of 152 cm) shows the tradition of bowing respectfully when entering the prayer room (signifying Javanese Architecture). Hindu-Javanese architectural elements should also be recorded in measured drawings.